ANALISIS KESALAHAN SISWA DALAM MENJAWAB SOAL LOGIKA MATEMATIKA PADA INDIKATOR BERPIKIR KRITIS MATEMATIS - Renata Teddy Ronny; Risma Amelia; Martin Bernard (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The question is in the form of a description test on the implementation of online learning during the Covid-19 pandemic which shows that most students have difficulty answering questions about mathematical logic material, this underlies the research. This problem occurs because students do not understand the existing statements and the concept of determining the truth value of a compound statement. The purpose of the research is to find out more about students' mistakes when answering mathematical description questions through analysis and description of some students' mistakes when answering questions on mathematical logic material, therefore this study uses descriptive methods with a qualitative approach. The research subjects were students of class XI OTKP (Office Automation and Governance) at one of the Vocational High Schools in Cimahi with a total of 18 students. The stages in this research are planning, implementation, and reporting. The results of the student description test of three questions were used to collect data. The analysis technique used is data reduction, presenting the data and then drawing conclusions. The results and discussion of this study indicate an average of 33.33% of students with low abilities. The percentage of student errors is 44.44% with moderate criteria and 22.22% with low criteria.